Dampak Sosial Ekonomi Pariwisata Dalam kehidupan Masyarakat Desa Panglipuran, Bangli, Bali - Andika Prihantara; Yudha Eka Ardiansyah; Habibah Habibah; Siska Febrina Rahmawati; Dewi Fitri Septiani; Teti Safari (Lembaga Pengembangan Kinerja Dosen, 2025)
This study examines the social, economic, and tourism impacts on the lives of the community in Penglipuran Tourism Village. The research highlights that the growth of tourism significantly increases local income by approximately 150–300%, fosters the creation of new business opportunities, and contributes to the preservation of Balinese culture and traditions. Tourism development not only strengthens the village’s cultural identity but also enhances social cohesion through community-based tourism initiatives. In addition, the adoption of digital technologies, such as cashless payment systems and electronic ticketing, has improved transaction efficiency, transparency, and market expansion, while also providing better services for visitors. Despite these benefits, several challenges have emerged, including growing environmental pressures, waste management issues, and the potential widening of economic inequality between residents directly involved in tourism and those who are not. These challenges indicate that tourism development can also create socio-economic gaps and place strains on the village’s natural resources if not managed carefully. Therefore, sustainable tourism management becomes crucial in balancing cultural preservation, economic equity, and environmental protection. This study suggests that policies integrating community participation, equitable economic distribution, and environmental sustainability are essential to ensure long-term positive impacts. Ultimately, Penglipuran Tourism Village can serve as a model for sustainable rural tourism development in Indonesia and beyond.